PERBANDINGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA YANG BELAJAR MENGGUNAKAN PENDEKATAN SAVI (SOMATIS AUDITORI VISUALINTELEKTUAL) DAN SISWA YANG BELAJAR DENGAN PENDEKATAN KONTEKSTUAL - Adzima, Khaola Rachma; Sudaryati, Sri; Wijaksana, Aris Hadiyan (Universitas Esa Unggul, 2019)
AbstractThis study aims to find out whether there are differences in mathematical problem solving abilities of students who learn using the SAVI approach and students who learn to use a contextual approach in junior high school. The research was carried out at SMP Negeri 255 Jakarta in April to May 2013. The research method used was quasi-experimental or quasi-experimental. The sampling technique uses the two stage random sampling technique. The first stage is simple random sampling to randomly select one of the two mathematics subject teachers who teach in class VII. The second stage is the cluster sampling cluster to determine two experimental classes that will be the research sample. Based on the results of the data analysis prerequisite test, it was found that the data of the two samples came from populations that were normally distributed, homongen, and there were similarities in average. Hypothesis testing uses two-party t-test with significance level and 58 degrees of freedom. The average test results of the mathematical problem-solving ability of the experimental class 1 are 71,417, while the average test results of the mathematical problem solving ability of experimental class 2 are 60.5. Based on the results of calculations, obtained meaningful values and values, then H0 is rejected, so it can be concluded that there are differences in mathematical problem solving abilities of students who learn using the SAVI approach and students who learn to use a contextual approach.Ã‚Â Keywords: SAVI, problem solving, contextual approachÃ‚Â AbstrakPenelitian ini bertujuan untukmengetahuiapakah terdapat perbedaan kemampuan pemecahan masalah matematissiswa yang belajar menggunakan pendekatan SAVI dan siswa yang belajar menggunakan pendekatan Ã‚Â kontekstual di SMP. Penelitian dilaksanakan di SMP Negeri 255 Jakarta pada bulan April sampai dengan bulan Mei 2013. Metode penelitian yang digunakan adalah quasi experiment atau eksperimen semu. Teknik pengambilan sampel menggunakan teknik two stage random sampling. Stage pertama yaitu simple random sampling untuk memilih secara acak satu dari dua guru mata pelajaran matematika yang mengajar di kelas VII. Stage kedua yaitu cluster randomsampling untuk menentukan dua kelas eksperimen yang akan menjadi sampel penelitian. Berdasarkan hasil uji prasyarat analisis data, diperoleh bahwa data kedua sampel berasal dari populasi yang berdistribusi normal, homongen, dan terdapat kesamaan rata-rata. Pengujian hipotesis menggunakan uji-t dua pihak dengan taraf signifikansi dan derajat kebebasan 58. Rata-rata hasil tes kemampuan pemecahan masalah matematis kelas eksperimen 1 adalah 71,417, sedangkan rata-rata hasil tes kemampuan pemecahan masalah matematis kelas eksperimen 2 adalah 60,5. Berdasarkan hasil perhitungan, diperoleh nilai Ã‚Â dan nilai Ã‚Â yang berarti , maka H0 ditolak, sehingga dapat disimpulkan bahwa terdapat perbedaan kemampuan pemecahan masalah matematis siswa yang belajar menggunakan pendekatan SAVI dan siswa yang belajar menggunakan pendekatan kontekstual.Ã‚Â Kata kunci: SAVI, pemecahanmasalah, pendekatan kontekstual